Trials on Cultivation of Some Medicinal and Aromatic Plants in Punjab - Singh, Jagjit (Indian Forester, 1964)
In this paper cultivation trials of 12 indigenous and exotic, medicinal and aromatic plants, carried out in various forest research nurseries in the hills and plains of Punjab State have been summarised. The results of analysis of materials thus produced and yield obtained have been given where available. Under results in the end the species considered suited to different areas of the State, have been noted.